Advances in Information and Communication Technologies for Adapting Agriculture to Climate Change Proceedings of the International Conference of ICT for Adapting Agriculture to Climate Change (AACC'17), November 22-24, 2017, Popayán, Colombia (Advances in Intelligent Systems and Computing,, 2018)
This book presents novel communication technology solutions to address the effects of climate change and climate variability on agriculture, with a particular focus on those that increase agricultural production. It discusses decision support and early warning systems for agriculture; information technology (IT) supporting sustainable water management and land cover dynamics; predictive of crop production models; and software applications for reducing the effects of diseases and pests on crops. Further topics include the real-time monitoring of weather conditions and water quality, as well as food security issues. Featuring the proceedings of the International Conference of ICT for Adapting Agriculture to Climate Change (AACC'17), held on November 22-24, 2017, in Popayán, Colombia, the book represents a timely report and a source of new ideas and solutions for both researchers and practitioners active in the agricultural sector around the globe.